Effectiveness of m-Learning Applications for Design and Technology Subject - A., Shah; Suhailiezana, Suhailiezana; Che Kob, Che Ghani; M, Khairudin (International Journal of Interactive Mobile Technologies (iJIM), 2019)
This study aims to evaluate the effectiveness of teaching aids using M-Learning application for Design and Technology Subjects. A total of 30 students Design and Technology subjects Form 1 of Kubang Kerian High School, Kelantan have answered the questionnaire. This questionnaire consists of five constructs namely Information design, Interaction design, showcase design and Training design (Sketch).This app was developed using ADDIE model. The overall findings of the research showed that the students were difficult to understand the topic of Pictorial Sketch was 2.45 at moderate level. After the study was conducted with the application of EZ Pictorial, the overall study findings rose at a high level of 4.64. This app enhances the level of understanding of the students and provides students with a fun learning situation.It is believed that this app will encourage student to learn difficult subject thus increase the performance of student achievement.